Predictive Value of Coagulation Markers Concerning Clinical Outcome 90 Days after Anterior Myocardial Infarction - Dempfle, Carl-Erik; Kontny, Frederic; Abildgaard, Ulrich (Thrombosis and Haemostasis, 1999)
To study the predictive value of coagulation markers concerning clinical outcome, prothrombin fragment F1.2 (F1.2), fibrin monomer antigen (FM), D-Dimer (DD), and fibrinogen were measured in plasma samples drawn 2 and 7 days after acute myocardial infarction (AMI) in 314 consecutive patients randomized in a clinical trial of low molecular weight heparin (Dalteparin) (the FRAMI trial). Placebo-treated patients suffering death or new AMI within 90 days had significantly higher levels at day 2 of FM (Enzymun-Test FM), and DD (TINAquant D-dimer) (p = 0.001 and 0.02, respectively), but not F1.2 (Enzygnost F1.2 micro), relative to those without serious clinical events. At day 7 all three coagulation activation markers were significantly higher in patients with subsequent adverse clinical outcome. The Dalteparin group had significantly lower levels of these markers as compared to the placebo group. Left ventricular (LV) thrombus formation was not associated with changes in coagulation activation. However, patients with thrombus had significantly higher fibrinogen levels than those without thrombus (p = 0.004 day 2), independent of treatment group. Thus, markers of coagulation activation may be useful in stratification of patients when estimating risk for adverse clinical outcome after AMI. Furthermore, elevated fibrinogen levels are associated with increased risk of LV thrombus formation.